Association between airborne particulate matter and renal function: An analysis of 2.5 million young adults. (February 2021) - Li, Qin; Wang, Yuan-Yuan; Guo, Yuming; Zhou, Hong; Wang, Qiao-Mei; Shen, Hai-Ping; Zhang, Yi-Ping; Yan, Dong-Hai; Li, Shanshan; Chen, Gongbo; Lin, Lizi; He, Yuan; et al.
Highlights: Each increase of 10 μg/m 3 in PM1 was associated with decreased eGFR by 0.64%. Each increase of 10 μg/m 3 in PM2.5 was associated with decreased eGFR by 0.72%. Associations between eGFR and PM were higher in females compared to males. Association with PM1 were weaker than that with other fractions included in PM2.5. Abstract: Background: Limited studies have examined the impact of airborne particulate matter of 2.5 μm or less (PM2.5 ) on renal function. No study has examined the effect of PM1, which is small enough to reach the blood circulation. We examined whether exposure to PM1 or PM2.5 affected renal function of young Han Chinese. Method: We included 2, 546, 047 young adults who were aged 18 to 45 years, being Han ethnicity and had no chronic disease from a Chinese national birth cohort. Serum creatinine (Scr) of each participant was measured during the baseline examination. Estimated glomerular filtration rate (eGFR) were calculated for each participant using the latest Chronic Kidney Disease Epidemiology Collaboration equation. One-year average exposure to PM1 and PM2.5 prior to the health examination for each participant were estimated using machine learning models with satellite remote sensing information. Generalized additive mixed models were used to estimate associations between PM1 or PM2.5 and renal function after adjusting for detailed individual variables. Results: A 10 μg/m 3 increment in PM1 exposure was associated with −0.95% (95%CI: −1.04%, −0.87%) difference of eGFR in females and −0.37% (95%CI: −0.44%, −0.31%) in males. For PM2.5, the corresponding difference of eGFR was −0.99% (95%CI: −1.05%, −0.93%) in females and −0.48% (95%CI: −0.53%, −0.43%) in males, respectively. Associations between eGFR and PM were higher in females compared to males ( p  < 0.05 for interaction test). Association with PM1 were weaker than that with other fractions included in PM2.5 . Participants who worked as farmers, were of normal weight, were not exposed to tobacco smoking, did not drink alcohol, had higher associations between eGFR and PM than their counterparts ( p  < 0.05 for interaction test). Conclusion: Exposure to PM1 and PM2.5 was associated with reduced renal function among Han Chinese at reproductive age.